50 economics classics : your shortcut to the most important ideas on capitalism, finance, and the global economy - Butler-Bowdon, Tom (London : Nicholas Brealey Publishing, 2017)
Economics drives the modern world and shapes our lives, but few of us feel we have time to engage with the breadth of ideas in the subject. 50 Economics Classics is a guide to two centuries of discussion of finance, capitalism and the global economy. From Adam Smith's Wealth of Nations to Thomas Piketty's bestseller Capital in the Twenty-First Century, here are the great reads, seminal ideas and famous texts clarified and illuminated for all.
Includes bibliographical references.
ESS
Hye Trade International
Keywords: Economics; Economics literature; Economics -- Bibliography; Economic analysis; BUSINESS & ECONOMICS -- Economic History; BUSINESS & ECONOMICS -- Economics; BUSINESS & ECONOMICS -- Reference; Economics; Economics literature; Bibliographies; Bibliography; Bibliographies